The evaluation of dynamic thiol/disulfide homeostasis in papillary thyroid carcinoma (Annals of Medical Research, 2023)
Aim: The aim of this presented article is to analyze the correlation between thiol/disulfide homeostasis (TDH) and papillary thyroid carcinoma (PTCA) and to investigate whether there is an effect of TDH on the development of PTCA.Materials and Methods: Preoperative venous blood sampling was obtained from the patients having applied to our hospital due to euthyroid nodular goiter and detected with suspected malignancy or malignant cytology in FNAB, according to the BETHESDA system. Those whose postoperative histopathological results proved the presence of PTCA were involved in this study. Healthy volunteers who were without any thyroid nodules and thyroid dysfunction.Results: The number of participants in the patient and control groups was 34 and 101, respectively. Compared to the control group, native thiol (μmol/L), total thiol (μmol/L), and native thiol/total thiol × 100 values were ascertained to be lower in the patient group with PTCA; however, these values were not statistically significant. Disulfide, disulfide/native thiol × 100, and disulfide/total thiol × 100 values were detected to be lower in the patient group with PTCA, but not statistically significant. When the patients with PTCA were assessed within themselves, TDH parameters were not associated with the PTCA subtype, the number of foci, the presence of lymphovascular invasion, and the presence of metastatic lap. Conclusion: Considering the parameters of PTCA and TDH, the results were not statistically significant. And besides postoperative histopathological findings such as the PTCA subtype, the number of foci, the presence of lymphovascular invasion, and presence of metastatic lap were not correlated with THD parameters.
Keywords: Papillary thyroid carcinoma; Thiol/disulfide homeostasis; Oxidative stress